Female genital tuberculosis: Five case reports - Abdurrahman Kaya; Sibel Yildiz Kaya; Esra Zerdali; Ali Can (Gynecology and Minimally Invasive Therapy, 2021)
Female genital tuberculosis (FG-TB) is an important disease leading to substantial morbidity including infertility and abnormal vaginal bleeding. While the incidence of FG-TB is < 1% in a developed area, its incidence is >1% in developing countries. Due to its subtle presentation, many cases are overlooked and diagnosed incidentally. Accordingly, the actual incidence of FG-TB is unknown. The definitive diagnosis of the disease is based on histopathological or microbiological examination but in most cases, the bacteriological test is overlooked. In addition, there is no specific laboratory or imaging evaluation to distinguish FG-TB from others. The first step in the diagnosis of FG-TB is suspicion of the disease. In the case of infertility, FG-TB should be included in the differential diagnosis in developing countries after excluding other common diseases and tissue biopsy should be sent for not only histopathology but also microbiological investigations.